Sensitivitas Hidrograf Satuan Di Sungai Batang Lubuh Dengan Menggunakan Hidrograf Satuan Sintetik Clark Dalam HEC-HMS - Isdianto Isdianto; Yohanna Lilis Handayani; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The method transforming of rain in HEC-HMS when applied on a DAS, it will show a different response in accordance with the selected method. Therefore it needs to known about the best transforming for sub DAS Rokan Kanan. Process on HEC-HMS program among others input data and calibration. Calibration process has six method Recession – Ratio to Peak, Clark Unit Hidrograph Time Of Concentration, Recession – Initial Discharge, Recession – Recession Constant, Clark Unit Hidrograph – Storage Coefficient, and Initial and Constan-Constan Rate. Objective function which used are Peak-Weighted RMS Error, Percent Error Peak, Percent Error Volume. The result of calibration Peak-Weighted RMS Error method=58.48. Percent Error Peak method = 1.11 and Percent Error Volume method= 0.00. Sensitivity of changes peak discharge and changes volume at parameter Initial and Constan-Constan Rate and Recession-Recession Constant with each changes presentation -76,15% and 77,70%.Keywords: hydrological modeling, unit hidrograph, sensitivity, hec-hms